Spatial and Temporal Variation Characteristics of Forests and Analysis of Potential for Reconstruction of Water Conservation Forests in the Dongjiang River Basin from 1980 to 2020 - DAI Miaolin; LU Xiaoqi; ZANG Chuanfu; ZHU Ke; QIU Xintong; LUO Yiwen; ZHANG Weiqiang; GAN Xianhua (Renmin Zhujiang)
The Dongjiang River is the most important water source area in the Guangdong-Hong Kong-Macao Greater Bay Area,supplying water for the three mega-cities of Hong Kong,Shenzhen,and Guangzhou.The Dongjiang River Basin has abundant light and heat resources and sufficient rainfall,and it is one of the regions with the highest forest coverage rate in China.Since 1980,the land cover,especially the forest with the largest proportion in the Dongjiang River Basin,has changed significantly in the Dongjiang River Basin under the influence of natural factors,policy,and economic development.Therefore,how to scientifically plan and design afforestation projects and transform water conservation forests according to potential has become a hot social issue.The study was based on 30 m resolution land use and soil data of the Dongjiang River Basin from 1980 to 2020,and it combined with the data of Dongjiang River Source station and socio-economic index data.The study used spatial analysis and factor analysis to explore the spatial-temporal changes and driving mechanisms of forest cover in the Dongjiang River Basin from 1980 to 2020 and analyze the potential of water conservation forest reconstruction in the future.① From 1980 to 2020,the forest decreased continuously in the Dongjiang River Basin,with a total reduction of 998.81 km2.The changes were mainly concentrated in the south and north of the Dongjiang River Basin.In the northern part of the basin,a great deal of forest has been transformed into farmland,while in the southern part of the basin,a great deal of forest has been transformed into cities and countrysides or areas for industry,mining,and housing.② In the period of 1980—2020,the main factors affecting the change of forest area were the number of permanent residents,population density,GDP,output value of secondary and tertiary industries,output value of industry,agriculture,and forestry,total retail sales of social consumer goods,investment in fixed assets,and urban registered unemployment rate.③ The area for future reconstruction in the Dongjiang River Basin was 5 365 km2.The areas with high potential for reconstruction were mainly in the north and southeast parts of the basin.In the past 40 years,the forest area of the Dongjiang River Basin has continued to decrease and is strongly influenced by human activities.Water conservation forest has great potential to be transformed.